2018
DOI: 10.1159/000495567
|View full text |Cite
|
Sign up to set email alerts
|

Modesty, Objectification, and Disordered Eating Patterns: A Comparative Study between Veiled and Unveiled Muslim Women Residing in Kuwait

Abstract: Background: The common thread running through all forms of sexual objectification is the experience of being treated as a body (or collection of body parts) valued predominantly for its use to (or consumption by) others. If girls and women adopt a peculiar view of the self, an effect called self-objectification, this may contribute to depression, sexual dysfunction, and eating disorders. The objective of this study is to investigate the impact of modesty (in terms of veiling, i.e., hijab) on objectification, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…In contrast to previous work (e.g., Swami et al, 2014 ; Al-Mutawa et al, 2019 ), the Muslim women in the present sample who wore a Hijab or Niqab did not significantly differ on any measure from the Muslim women who did not. This finding should be interpreted with caution for several reasons.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous work (e.g., Swami et al, 2014 ; Al-Mutawa et al, 2019 ), the Muslim women in the present sample who wore a Hijab or Niqab did not significantly differ on any measure from the Muslim women who did not. This finding should be interpreted with caution for several reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…The sample size of Muslim women in this study was relatively small and this analysis was not central to our hypotheses. We did not collect data on modest dress more broadly, including covering of other body parts, that may have an influence of body image ( Al-Mutawa et al, 2019 ). Importantly, our question about wearing a niqab or hijab was biased toward women who practice Islam; therefore, Hindu women who chose to wear a kameez or a veil to cover their chest or body would not have been captured.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to findings in other settings, urbanization has been associated with a preference for thinness (Jackson et al, 2003 ), and research has pointed to the role of sociocultural factors in body image concerns, including the role of media (Tayyem et al, 2016 ; Saghir and Hyland, 2017 ) and the internalization of appearance ideals (Melki et al, 2015 ; Zainal et al, 2020 ). Perhaps in this geographic area more than others, the role of cultural and religious values and behaviors has been explored, with findings suggesting that the relationships are complex and require further disentangling (Al-Mutawa et al, 2019 ; Sidi et al, 2020 ).…”
Section: Empirical Evidence Across Countriesmentioning
confidence: 99%
“…Indeed, a study showed that despite sizes, women are equally objectified when they dress in revealing clothes (Holland & Haslam, 2013). It is essential to note, however, that this does not imply that objectification is the sole responsibility of women, as social phenomena demonstrate that modestly-dressed women are not completely immune to such experiences (Al-Mutawa et al, 2019;Zahara, 2023aZahara, , 2023b).…”
Section: Reneementioning
confidence: 99%